Golden Gate Cloning-Compatible DNA Replicon/2A-Mediated Polycistronic Vectors for Plants - Lee, Jae Hoon; Won, Hyo Jun; Oh, Eun-Seok; Oh, Man-Ho; Jung, Je Hyeong (Frontiers in Plant Science, 2020)
The expression of multiple proteins and high-throughput vector assembly system are highly relevant in the field of plant genetic engineering and synthetic biology. Deployment of the self-cleaving 2A peptide that mediates polycistronic gene expression has been an effective strategy for multigene expression, as it minimizes issues in coordinated transgene regulation and trait staking in plants. However, efficient vector assembly systems optimized for 2A peptide-mediated polycistronic expression are currently unavailable. Furthermore, it is unclear whether protein expression levels are influenced by the transgene position in the polycistronic expression cassette. In this paper, we present Golden Gate cloning-compatible modular systems allowing rapid and flexible construction of polycistronic expression vectors applicable for plants. The genetic modules comprised 2A peptides (T2A and P2A)-linked tricistron expression cassette and its acceptor backbones, named pGO-DV1 and pGO-DV2. While both acceptor backbones were binary T-DNA vectors, pGO-DV2 was specially designed to function as a DNA replicon enhancing gene expression levels. Using the Golden Gate cloning, a set of six tricistronic vectors was constructed, whereby three transgenes encoding fluorescent proteins (mCherry, eYFP, and eGFP) were combinatorially placed along the expression cassette in each of the binary vectors. Transient expression of the construct in tobacco leaves revealed that the expression levels of three fluorescent proteins were comparable each other regardless of the gene positions in the tricistronic expression cassette. pGO-DV2-based constructs were able to increase protein expression level by up to 71%, as compared to pGO-DV1-based constructs.